HISTORIOGRAPHY OF JAPANESE “ISLAMIC POLICY” IN INDONESIA - Saiful Umam (Islamika Indonesiana, 2014)
Japanese occupation in Southeast Asia, specifically in Indonesia, was very shortcompared to the Western colonialism in the region. It was only about three and halfyears, 1942-1945. However, many scholars have studied the period and a number of books and articles have been produced. Almost all of them note the importance of the short period in changing socio-political condition of the occupied areas.The propaganda of Japan when she landed to the region was to build “the Greater East Asia,” and “Co-Prosperity Sphere.” To realize that, Japan tried to win support from as many population as possible in the occupied territory, so that she cooperated with those who really had influence on the grass-root level with the objective that mobilization would be successful. Japan was in need of natural and human resources for war purposes. In Indonesia, more precisely in Java, Japan used ulama or kiyai (religious leaders/scholars) as her main agents of the propaganda. This is why the term “Islamic policy” is usually used by scholars who study the Japanese occupation in the region.